THE EFFECT OF USING A COUNTDOWN TIMER ON THE SIGNALIZED INTERSECTIONS PERFORMANCE IN MALANG CITY: Pengaruh Penggunaan Countdown Timer Pada Simpang Bersinyal di Kota Malang - Maliq, Tatang Maulana; Sulistio, Harnen; Djakfar, Ludfi; Sulistyono, Sonya (Jurnal Rekayasa Sipil dan Lingkungan, 2018)
The high growth of the population in Malang will trigger an increase in the activity of its, resulting in increased traffic. Increased traffic demands will add to traffic congestion problems on roads and intersections. One way of traffic engineering to improve signaled intersection performance is to equip traffic signals with countdown timers. This additional instrument serves to inform the duration of the signal setup time. This study aims to determine the effect of countdown timer use on saturation flow, performance and safety factor signalized intersection in Malang. The paired sample t-teste statistical method is used to see the influence of the countdown timer on saturation flow, and the impact on the performance and safety of the intersection arm. The use of countdown timer can increase the value of saturation flow, so the capacity of the intersection also increased 5-22% with decreasing delay time 5-13 sec/smp. But the less positive impact on the safety factor intersection, because there is an increase in the movement of vehicles before the green time. Tingginya pertumbuhan jumah penduduk di Kota Malang akan memicu peningkatan aktifitas penduduk sehingga berdampak pada meningkatnya lalu lintas. Peningkatan tuntutan lalu lintas akan menambah masalah kemacetan lalu lintas pada ruas jalan dan simpang. Salah satu cara rekayasa lalu lintas untuk meningkatkan kinerja simpang bersinyal adalah melengkapi sinyal lalu lintas dengan countdown timer. Instrumen tambahan ini berfungsi menginformasikan durasi waktu pengaturan sinyal. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan countdown timer terhadap arus jenuh , kinerja dan faktor keselamatan simpang bersinyal di Kota Malang. Metode statistik paired sample t-teste digunakan untuk melihat pengaruh countdown timer terhadap arus jenuh, dan dampak pada kinerja serta keselamatan lengan simpang. Penggunaan countdown timer mampu meningkatkan nilai arus jenuh, sehingga kapasitas lengan simpang juga mengalami peningkatan 5-22% dengan penurunan waktu tundaan 5-13 detik/smp. Tetapi kurang berdampak positif terhadap faktor keselamatan simpang, karena terjadi peningkatan pergerakan kendaraan sebelum waktu hijau.